2020
DOI: 10.1264/jsme2.me19110
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Harmful Bloom-Forming Cyanobacterium, <i>Microcystis aeruginosa</i>, in 88 Freshwater Environments across Japan

Abstract: Microcystis aeruginosa was quantitatively surveyed in 88 freshwater environments across Japan within 3 weeks in 2011. In order to clarify the distribution pattern of M. aeruginosa at the intra-species level, three major genotypes, which were defined by 16S-23S rRNA inter-transcribed-spacer (ITS) regions, were selectively detected using quantitative real-time PCR assays. Of the 68 sites at which the Microcystis intergenic-spacer region of the phycocyanin (IGS-PC) gene was detected, the M. aeruginosa morphotype-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
(65 reference statements)
1
2
0
Order By: Relevance
“…The N2O synthesis rates reported during our study are in the same order of magnitude as the rate previously reported for members of the green microalgae, cyanobacteria, and diatoms (Bauer et al, 2016;Plouviez et al, 2019). Our findings therefore support past predictions of the global relevance of photosynthetic N2O emissions from eutrophic aquatic bodies as Microcystis is globally found and often the dominant genus in these ecosystems (Qian et al, 2010;Kataoka et al, 2020;Zhou et al, 2020). Further research is now needed to quantify N2O emissions from eutrophic aquatic ecosystems where M. aeruginosa abounds.…”
Section: Potential Environmental Implicationssupporting
confidence: 89%
See 2 more Smart Citations
“…The N2O synthesis rates reported during our study are in the same order of magnitude as the rate previously reported for members of the green microalgae, cyanobacteria, and diatoms (Bauer et al, 2016;Plouviez et al, 2019). Our findings therefore support past predictions of the global relevance of photosynthetic N2O emissions from eutrophic aquatic bodies as Microcystis is globally found and often the dominant genus in these ecosystems (Qian et al, 2010;Kataoka et al, 2020;Zhou et al, 2020). Further research is now needed to quantify N2O emissions from eutrophic aquatic ecosystems where M. aeruginosa abounds.…”
Section: Potential Environmental Implicationssupporting
confidence: 89%
“…Further research is now needed to quantify N2O emissions from eutrophic aquatic ecosystems where M. aeruginosa abounds. This is especially timely considering that the frequency and geographic distribution of harmful algae blooms have increased due to anthropogenic activities (Paerl et al, 2018;Kataoka et al, 2020).…”
Section: Potential Environmental Implicationsmentioning
confidence: 99%
See 1 more Smart Citation